The Characteristic of Technogenic Transformation of the Springs Discharge Chemical Composition in the Area of Salt Mining: An Example of the Upper Kama Deposit - P. A. Belkin (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2018)
Study of influence of the potash industry facilities on the hydrochemical properties of groundwater was conducted in the central part of Upper Kama potash salt deposit in vicinity of city of Solikamsk (Perm Region). Data collected during the monitoring of underground waters composition outside the development area and in the springs close to operating mines were generalized. Results of waters samples study revealed considerable variation in the chemical composition. The obtained data were analysed using statistical methods. The ionic composition of underground waters from the operating areas of potash mines was enriched with chlorides, bromides, and cations of sodium, potassium, calcium, magnesium, and ammonium. Hydrochemical indicators of change of microelement composition were manganese, cobalt, arsenic, vanadium, nickel, antimony, barium, strontium, selenium.